Generation of Codon-Optimized Fad3 Gene Transgenic Bovine That Produce More n-3 Polyunsaturated Fatty Acids - Guanghua Su; Zhuying Wei; Chunling Bai; Danyi Li; Xiaoyu Zhao; Xuefei Liu; Lishuang Song; Li Zhang; Guangpeng Li; Lei Yang (Animals)
Polyunsaturated fatty acids (PUFAs) such as linoleic acid (18:2, n-6) and α-linolenic acid (18:3, n-3) are essential for the growth, development, and well-being of mammals. However, most mammals, including humans, cannot synthesize n-3 and n-6 PUFAs and these must be obtained through diet. The beneficial effect of converting n-6 polyunsaturated fatty acids (n-6 PUFAs) into n-3 polyunsaturated fatty acids (n-3 PUFAs) has led to extensive research on the flax fatty acid desaturase 3 (Fad3) gene, which encodes fatty acid desaturase. Still, the plant-derived Fad3 gene is used much less in transgenic animals than the Fat-1 gene from Caenorhabditis elegans. To address this problem, we used somatic cell nuclear transfer (SCNT) technology to create codon-optimized Fad3 transgenic cattle. Gas chromatographic analysis showed that the n-3 PUFA content of transgenic cattle increased significantly, and the ratio of n-6 PUFAs to n-3 PUFAs decreased from 3.484 ± 0.46 to about 2.78 ± 0.14 (p < 0.05). In conclusion, Fad3 gene knock-in cattle are expected to improve the nutritional value of beef and can be used as an animal model to study the therapeutic effects of n-3 PUFAs in various diseases.